Resistance exercise improves metabolic parameters and changes adipocyte-derived leptin: a comparison between genders in untrained adults - Gustavo Ribeiro da Mota; Fábio Lera Orsatti; Maria Andréia Delbin; Angelina Zanesco
Abstract This study examined gender differences after resistance exercise (RE) by measuring fasting plasma levels of creatine kinase, lipid profile, blood glucose, adiponectin, tumor necrosis factor alpha (TNF-α), and leptin. Thirteen women (23.6 ± 7.3 years) and 11 men (29.5 ± 9 years) were enrolled in the study. Two bouts of RE were performed on two different occasions separated by 48 h each. Blood samples were collected and analyzed at baseline and 15 h after the last RE session. Increased creatine kinase levels and improvements in lipid profile and blood glucose were found for both genders. No changes in adiponectin and TNF-α levels were observed for both genders, but leptin levels were reduced (p < 0.05) only for women after RE. Collectively, our findings clearly show that RE was effective in lowering blood glucose and that this effect was not accompanied by changes in adiponectin levels in healthy subjects, indicating that RE is still an important tool for the prevention of metabolic diseases. Furthermore, two sessions of RE promoted a reduction in leptin levels in women, even though no changes in body weight were found, showing that RE is an interesting approach to study obese patients and metabolic regulation.